Beyond Teenage and Young Adult Cancer Care: Care Experiences of Patients Aged 25–39 Years Old in the UK National Health Service. Issue 8 (August 2021) - Lidington, E.; Darlington, A.S.; Vlooswijk, C.; Beardsworth, S.; McCaffrey, S.; Tang, S.; Stallard, K.; Younger, E.; Edwards, P.; Ali, A.I.; Nandhabalan, M.; Din, A.; et al.
Abstract: Aims: Adolescents and young adults aged 15–39 years with cancer face unique medical, practical and psychosocial issues. In the UK, principal treatment centres and programmes have been designed to care for teenage and young adult patients aged 13–24 years in an age-appropriate manner. However, for young adults (YAs) aged 25–39 years with cancer, little access to age-specific support is available. The aim of this study was to examine this possible gap by qualitatively exploring YA care experiences, involving patients as research partners in the analysis to ensure robust results. Materials and methods: We conducted a phenomenological qualitative study with YAs diagnosed with any cancer type between ages 25 and 39 years old in the last 5 years. Participants took part in interviews or focus groups and data were analysed using inductive thematic analysis. Results were shaped in an iterative process with the initial coders and four YA patients who did not participate in the study to improve the rigor of the results. Results: Sixty-five YAs with a range of tumour types participated. We identified seven themes and 13 subthemes. YAs found navigating the healthcare system difficult and commonly experienced prolonged diagnostic pathways. Participants felt under-informed about clinical details and the long-term implications of side-effects on daily life. YAs found online resources overwhelming but also a source of information and treatment support. Some patients regretted not discussing fertility before cancer treatment or felt uninformed or rushed when making fertility preservation decisions. A lack of age-tailored content or age-specific groups deterred YAs from accessing psychological support and rehabilitation services. Conclusions: YAs with cancer may miss some benefits provided to teenagers and young adults in age-tailored cancer services. Improving services for YAs in adult settings should focus on provision of age-specific information and access to existing relevant support. Highlights: Young adults (YAs) aged 25–39 years found navigating the healthcare system difficult. Participants felt under-informed about clinical details and impacts of side-effects. Some YAs did not discuss fertility before cancer treatment or felt uninformed about the risks. Lack of age-relevance deterred YAs from using psychological and rehabilitation services. Improving services for YAs should focus on timely provision of age-specific information.